Recurrence after piecemeal hot-snare endoscopic mucosal resection of 10–20-mm nonpedunculated colorectal polyps: a multicenter cohort study - Maas, Michiel H. J.; Hazewinkel, Yark; Terhaar Sive Droste, Jochim S.; Schrauwen, Ruud W. M.; Tan, Adriaan C.; Koehestanie, Parweez; van Kouwen, Mariëtte C. A.; Siersema, Peter D. (Endoscopy, 2025)
Guidelines are equivocal on the need for early surveillance colonoscopy (ESC) after piecemeal endoscopic mucosal resection (pEMR) of 10–20-mm nonpedunculated colorectal polyps (NPCPs). This study assessed recurrence rates and associated factors at ESC following hot-snare pEMR of 10–20-mm NPCPs.A retrospective, multicenter cohort study was performed at five hospitals in the Netherlands. Patients undergoing pEMR of 10–20-mm NPCPs (2014–2021) and referred for ESC (range 3–9 months) were included. The primary outcome was recurrence rate at ESC. Secondary outcomes included scar identification rates, both overall and at tattooed sites. A mixed-effects model was used to identify factors associated with recurrence.389 patients undergoing pEMR of 426 NPCPs 10–20 mm (median 15 mm, interquartile range 12.8–20.0 mm) were included. Overall, 262 scars (61.5%; 95%CI 56.8–66.0) and 81.6% of tattooed sites were identified at ESC. The recurrence rate was 35/426 (8.2%; 95%CI 6.0–11.2) overall and 35/262 (13.4%; 95%CI 9.8–18.0) when the scar was identified. Median recurrence size was 5 mm, without high grade dysplasia. No NPCP characteristics were associated with recurrence.This real-world study found a substantial recurrence rate after hot-snare pEMR of NPCPs sized 10–20mm at ESC. ESC scar identification was moderate but improved with tattoo placement. Although early surveillance could be considered to avoid missing recurrence, the small recurrence size and absence of high grade dysplasia suggest that modestly extending the interval beyond that of our study may still allow timely detection of recurrences and metachronous lesions.